2019
DOI: 10.1063/1.5110296
|View full text |Cite
|
Sign up to set email alerts
|

Efficient sound radiation using a bandgap structure

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The existence of Bragg gap in a periodic composite material pipe has been demonstrated theoretically 34 and experimentally 35 with the goal of reducing and controlling the elastic vibrations of the pipe. A pipe filled with air can also carry the acoustic pressure generated by a loudspeaker that can be modulated with the internal structuration of the rigid solid part 36,37 . Xiao et al 38 demonstrated the existence of topologic states at the interface of two phononic crystals having different topological band gap characteristics.…”
Section: In 1dmentioning
confidence: 99%
“…The existence of Bragg gap in a periodic composite material pipe has been demonstrated theoretically 34 and experimentally 35 with the goal of reducing and controlling the elastic vibrations of the pipe. A pipe filled with air can also carry the acoustic pressure generated by a loudspeaker that can be modulated with the internal structuration of the rigid solid part 36,37 . Xiao et al 38 demonstrated the existence of topologic states at the interface of two phononic crystals having different topological band gap characteristics.…”
Section: In 1dmentioning
confidence: 99%
“…where K = R + SH −1 Q, M = Z + TH −1 Q, and W(ω) = U(ω) + V(ω)H −1 Q. For a given frequency ω, by solving Equation (25), the coefficient vector a can be achieved, and then p can be determined by Equation (16). The transverse displacement of the base plate can be further obtained by Equation (4).…”
Section: Forced Response Of the Finite Lr Plate With Elastic Boundarymentioning
confidence: 99%
“…Guo et al [24] derived the average radiation efficiency of a sandwich plate with periodically inserted LR resonators theoretically. Recently, Jung et al [25,26] used the LR band gaps to increase the efficiency of sound radiation employing defect modes on a phononic crystal. Although research has been conducted focusing on acoustic radiation in LR structures, more studies can be done to further obtain valuable acoustical characteristics of the LR structure in the low-frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…We present a mode elimination technique using a band gap (BG) structure, which forbids the propagation of bending waves within a frequency band called a band gap (or also called stop band) [22][23][24][25]. Usually, BG structures consist of a periodic arrangement of elements such as scatterers [26], resonators [27], and with use of inertial amplification [28], which make wavenumber imaginary within a BG range. Due to the imaginary wavenumber, bending waves decay exponentially and become unlikely to reflect from the boundaries; thus, the BG structure allows no standing waves and no modes within the BG [26].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, BG structures consist of a periodic arrangement of elements such as scatterers [26], resonators [27], and with use of inertial amplification [28], which make wavenumber imaginary within a BG range. Due to the imaginary wavenumber, bending waves decay exponentially and become unlikely to reflect from the boundaries; thus, the BG structure allows no standing waves and no modes within the BG [26]. Fig.…”
Section: Introductionmentioning
confidence: 99%